FORENSIC ACCOUNTING AND CORPORATE SUSTAINABILITY IN BANGLADESHI COMPANIES: AN EMPIRICAL STUDY - Sen, Tarun; Raju, Md Raihan Ahmed Raju (International Journal of Accounting & Finance Review, 2025)
Sustainable corporate governance plays a vital role in enhancing transparency, accountability, and long-term organizational performance, particularly in emerging economies such as Bangladesh, where governance vulnerabilities remain persistent. Despite growing recognition of forensic accounting as a tool for strengthening internal controls and reducing financial misconduct, empirical evidence on its influence within Bangladeshi listed companies is limited. This study investigates the impact of forensic accounting on sustainable corporate governance. Data were collected via a structured questionnaire administered to professionals employed by listed companies, yielding 225 valid responses. Sustainable corporate governance was assessed using three core components: the Board of Directors (BOD), Audit Risk Committee (ARC), and Nomination and Remuneration Committee (NRC). Structural Equation Modeling (SEM) was utilized to examine the relationship between forensic accounting practices and sustainable corporate governance. The results reveal that forensic accounting has a significant positive effect on sustainable corporate governance, demonstrated by a path coefficient of 0.090, a standard error of 0.023, a t-value of 3.888, and a significance level of p < 0.01, thereby confirming the proposed hypothesis (H1). The findings indicate that applying forensic accounting enhances sustainable governance structures among Bangladeshi listed companies. Improvements were observed across the BOD, ARC, and NRC indicators, demonstrating that forensic accounting significantly strengthens decision-making processes, reinforces risk oversight, and enhances committee-level governance. Overall, the study provides empirical evidence that forensic accounting plays a measurable role in supporting the key structural components of sustainable corporate governance among Bangladesh’s listed firms. JEL Classification Codes: M42, M14, Q56.